2019
DOI: 10.1002/ajp.23017
|View full text |Cite
|
Sign up to set email alerts
|

Use of space and home range characteristics of Lepilemur mittermeieri, an endangered sportive lemur endemic to the Ampasindava peninsula, north‐west Madagascar

Abstract: Lepilemur mittermeieri, a little‐studied sportive lemur of north‐west Madagascar, endemic to the Ampasindava Peninsula, faces habitat loss through forest degradation and rapid fragmentation. Understanding its habitat requirement is the first step toward preservation of this threatened forest‐dependent species. In this study, we gathered data on the use of space and home range characteristics of L. mittermeieri. We studied individuals from early March to the end of June 2015 and 2016, in three sites of the Ampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Increased deforestation may also lead to more densely populated fragments, in turn reducing home range size for NSLs found within them, especially since females have territorial and nonoverlapping home ranges. This study reported home range sizes from 0.63 to 2.58 ha, with an average home range size of 1.15 ± 0.64 ha, which are comparable and often times larger than many reported home ranges for other Lepilemur species (Ganzhorn et al, 2004; Hladik & Charles‐Dominique, 1974; Mandl et al, 2018; Rasoloharijaona et al, 2006; Ratsirarson & Rumpler, 1988; Stalenberg, 2019; Wilmet et al, 2019). Known Lepilemur spp.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Increased deforestation may also lead to more densely populated fragments, in turn reducing home range size for NSLs found within them, especially since females have territorial and nonoverlapping home ranges. This study reported home range sizes from 0.63 to 2.58 ha, with an average home range size of 1.15 ± 0.64 ha, which are comparable and often times larger than many reported home ranges for other Lepilemur species (Ganzhorn et al, 2004; Hladik & Charles‐Dominique, 1974; Mandl et al, 2018; Rasoloharijaona et al, 2006; Ratsirarson & Rumpler, 1988; Stalenberg, 2019; Wilmet et al, 2019). Known Lepilemur spp.…”
Section: Discussionmentioning
confidence: 73%
“…Had we collected data from this individual who was located in such a highly anthropogenically utilized portion of MDF, we may have seen different results. However, other studies have indicated that Lepilemur species have shown the ability to persist in highly disturbed environments, despite reductions in habitat quality (Sawyer et al, 2017; Seiler et al, 2014; Wilmet et al, 2019). Most likely, NSLs exhibit similar abilities to persist in highly degraded and disturbed environments due to their ability to consume a diverse range of plant species and their solitary nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monkeys mainly inhabit forests and seldom have contact with humans [ 43 ]. The methods used were line transect sampling and camera traps in the second survey [ 45 , 46 , 47 ]. We divided the study area into 59 grids (2 km × 2 km) in ArcGIS (Version 10.4.1).…”
Section: Methodsmentioning
confidence: 99%
“…We assumed a constant population density for species across their AOH, thus ignoring potential edge effects. We consider this assumption justified because evidence suggests that Malagasy mammals (especially lemurs) are not edge sensitive (e.g., Lehman et al, 2006;Quemere et al, 2010;Wilmet et al, 2019). Because information on the population parameters (initial population density, population density at carrying capacity, intrinsic population growth rate, environmental stochasticity, and median dispersal distance) is lacking for many Malagasy mammals, we estimated these parameters based on allometric relationships (Appendix S1).…”
Section: Population Projectionsmentioning
confidence: 99%